Analysis of Bullying Phenomenon Among Fifth Grade Students of Public Elementary School 1 Kemiri in the 2024/2025 Academic Year - Niken Pratiwi; Sri Suwartini; Putri Zudhah Ferryka (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
State Elementary School 1 Kemiri is one of the elementary schools that has diverse student characters. In daily learning, various dynamics of social interactions emerge, including bullying behavior that still often occurs among fifth grade students. This phenomenon is of concern because it has a direct impact on the comfort of learning and the development of their social attitudes. Therefore, this study was conducted to reveal the forms of bullying that occur and to examine the influence of instilling Pancasila values ​​on preventing it. This study uses quantitative methods. Data were collected through interviews, observations, questionnaires, and surveys. Furthermore, the data were analyzed using a number of statistical tests, such as validity, reliability, normality, linearity, simple linear regression, and determination. The aim is to see to what extent the internalization of Pancasila values ​​is able to influence the reduction in bullying rates in schools. The results of the study showed that the dominant forms of bullying were verbal and social bullying. The factors underlying this behavior include the influence of the family environment, peer pressure, and exposure to social media. From the results of the data analysis, it is known that Pancasila values ​​play a significant role in reducing bullying behavior, with a contribution of 66%, while the rest is influenced by other factors that are not studied further. Thus, the instillation of Pancasila values ​​has proven to be important in supporting the creation of a safe and educational school atmosphere, as well as being a preventive effort in reducing bullying behavior at the elementary school level.